Incidence of bovine mastitis the “ dairy bascin” of the Southern “Agreste” zone in Pernambuco State, Brazil - Harrop, Mabel Hanna V.; Pereira, Lúcio José G.; Brito, José Renaldí F.; Mello, Antonia Maria B. de (Pesquisa Agropecuaria Brasileira, 2014)
The CMT test was used to examine 866 lactating cows of 20 farms situated in 6 counties of “Agreste Meridional” (Southern "Harsh") physiographic zone in Pernambuco, a state of Brazil. Most of the animals were crossbred, predominantly Zebu. At some farms the herd consisted in part of Holstein-Friesian cattle. The CMT revealed disturbance of milk secretion in 338 cows (39.1%), and bacteriological tests indicated an infection in the udders of 275 cows (31.7% of the total number examined). Bacteria isolated included Staphytococcus aureus, from 163 cows (59.2%); Streptococcus agalactiae, from 39 cows (14.1%); S. dysgalactiae, from 52 cows (18,9%); S. uberis, from 86 cows (31.2%); Corynebacterium pyogenes, from 4 cows (1.4%). Of the 2,997 quarters examined, 437 (14.5%) were affected by mastitis. This corresponds to an average rate of incidence of 1,58 infected quarter per cow.